The Effectiveness of Blended Learning Model on the Cells Material to Students’ Learning Outcomes and Conservation Behavior - Fahrudin, Dimas; Pukan, Krispinus Kedati (FMIPA UNNES, 2020)
Based on observations and interviews the results of learning activities are disrupted by the school ,teacher and student agenda. Obstacles in the learning process impact the learning objectives and lack of the classical submission of the classifications gained by the students. This research aims to know and describe the effectiveness of the application of blended learning models for learning outcomes and conservation attitudes of MAN 1 Surakarta students. This research uses quasi experiment. The design that has been used is Matching Pretest – Posttest Comparison Grub Design, two research samples consisting of male experiment classes and female experiments were given pretest, treatment and posttest. The population in the study was class XI of MAN 1 Surakarta student. The samples used are class XI MIA 4 and XI MIA 5. Analysis of the Posttest value using the N-gain test. The N-Gain test results show the difference in the learning outcomes of both experimental classes. Increased outcomes of female class higher (64%) than the male`s class (51%). Nevertheless based on the criteria N-gain both classes are included in the medium criteria. The number of students per N-gain criterion is also different, in the male experiment Class 7 students enter the high, 23 students are medium category and 6 students enter the low category while in the female class 16 students enter high category, 19 medium category and no entry category low. The entire sample submission was 76%, in the men's class of 69.5% and in the women's class 82.8% the results of the students ' attitude recapitulation showed that students in the class were higher than the son's grade, but both were still included in the excellent category. Teachers and students give good responses to the learning model applied. The conclusion of the study is the implementation of learning blended models to improve the learning outcomes and attitudes of the students ' responsibilities.